1989
DOI: 10.1152/ajpheart.1989.256.3.h613
|View full text |Cite
|
Sign up to set email alerts
|

Responses to acute hypoxemia in fetal sheep at 0.6-0.7 gestation

Abstract: A majority of previous studies of fetal responses to acute hypoxemia has focused on the response of the sheep fetus greater than 120 days of gestation when many regulatory systems have been established. To assess the response of younger, less well-developed fetuses, we exposed two groups of fetal sheep (I, 84-91 days; II, 97-99 days gestational age) to acute hypoxemia by giving the ewe a gas mixture containing 9% O2 to breathe. We decreased descending aortic PO2 in both groups of fetuses [I, 24 +/- 6 to 14 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 0 publications
6
71
1
1
Order By: Relevance
“…With models of maternal hypoxemia (e.g., high altitude or a low inspired oxygen fraction), fetal oxygenation falls while BP rises transiently, but then returns to normal, and then falls below normal [67,68,96,[103][104][105][106]. Perinatal hypoxic-ischemic encepatholpathy models that involve the entire body frequently use umbilical cord occlusion and are accompanied by reduced systemic fetal arterial oxygen tension and content [70,107,108].…”
Section: Pathophysiological Mechanisms Of Wmi Related To the Brachiocmentioning
confidence: 99%
“…With models of maternal hypoxemia (e.g., high altitude or a low inspired oxygen fraction), fetal oxygenation falls while BP rises transiently, but then returns to normal, and then falls below normal [67,68,96,[103][104][105][106]. Perinatal hypoxic-ischemic encepatholpathy models that involve the entire body frequently use umbilical cord occlusion and are accompanied by reduced systemic fetal arterial oxygen tension and content [70,107,108].…”
Section: Pathophysiological Mechanisms Of Wmi Related To the Brachiocmentioning
confidence: 99%
“…Matsuda et al (1992) reported that the cardiovascular and biophysical responses of the preterm sheep fetus to sustained hypoxemia were much less pronounced than those of more mature fetuses, and suggested that these differences might impact both survival and precision of antenatal assessment protocols. Boddy et al (1974) reported fetal tachycardia in response to induced hypoxemia in preterm fetuses (gestational day 100), as did Iwamoto et al (1989), Matsuda et al (1992), and Gleason et al (1990). These findings may relate to a predominance of sympathetic cardiac effects at earlier gestational ages.…”
Section: Discussionmentioning
confidence: 73%
“…It is unlikely that AVP and norepinephrine could maintain fetal redistribution of blood flow during chronic hypoxemia, given their tachyphylaxic effects (Miyake et al 1991). Iwamoto et al (1989) reported that in younger sheep fetuses, as in older fetuses, cerebral, myocardial, and adrenal blood flow increased, while pulmonary blood flow decreased with acute hypoxemia. These responses mature early and probably represent local vascular responses to decreased oxygen content.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations